Validitas dan Kepraktisan Modul Digital Berbasis Socio Scientific Issue - Nurdiyanti Nurdiyanti*; Muhammad Wajdi; Nurul Fadhilah (Universitas Syiah Kuala, 2022)
The development of science and technology that affects society has placed scientific literacy as an important concern by governments in various countries in the world, including Indonesia. The Indonesian government also seeks to encourage the improvement of scientific literacy skills in Indonesia. One of them is through the implementation of a curriculum that emphasizes the mastery of science process skills which is one of the elements of scientific literacy. In addition, learning in the 21st century, educators should integrate the use of technology in learning. The use of digital modules with socio scientific issue content is one way to answer these challenges. The purpose of this research is to develop a digital module using content related to scientific social issues that is valid and practical. This type of research is research and development (RD). With this module, it is expected to support the science literation skills of students as prospective biology teachers. The procedure of development module refers to the Alessi Trolip model which consists of three main stages, namely 1) plan, 2) design and 3) development. The validity of the module is assessed by media experts, material experts, and practitioners (lecturers on cell biology courses). Data processing used descriptive data analysis techniques. Based on the results of the analysis of data, the validity of the module from media experts is about 4.75 (valid), material experts amounted to 4.5 (very valid) and the validity value of practitioners amounted to 4.52 (very valid).